The experiences of critical nurses regarding staffing management in critical care units in private hospitals of the Cape Metropole - Anthonie, Ramona F. G. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MCurr)--Stellenbosch University, 2012.